EUTHANASIA REVIEW FROM APPLICABLE CRIMINAL LAW IN INDONESIA (Case Study Medan District Court) - Mega; Nelvitia Purba (Fox Justi : Jurnal Ilmu Hukum, 2022)
Apart from technological advances that have many positive effects, it's just that for some people think that these advances have negative effects as well. The negative influence in question is the human thought of a death. The negative influence of technological advances in health science causes the family of a patient or the patient himself to apply to medical personnel or doctors to hasten the death of a patient in order to relieve pain so that the patient can rest in peace and this is what we call euthanasia. In line with the title of this research, namely "Euthanasia Judging from the Criminal Law Applicable in Indonesia". The problems that will be discussed in this research are How is the application of the law related to euthanasia in the perspective of criminal law? What are the factors that cause someone to apply for euthanasia? What is the medical legal responsibility regarding medical officers (doctors) who perform euthanasia? This research approach uses normative juridical law research methods. This study uses primary data and tertiary data and data analysis in this study uses qualitative analysis. This study shows that the legal basis used for regulating euthanasia in positive law in Indonesia is Article 344 of the Criminal Code, and the factors that apply to euthanasia are generally severe illness with low life expectancy, frustration factors and economic or financial factors.